Maxim Gorky’s drama as a scientific research and creative development in China - Fei Li; Irina V. Monisova (RUDN Journal of Studies in Literature and Journalism, 2019)
The research attempts to systematize and summarize the works of Chinese philologists on the drama of M. Gorky. The research shows how the tradition of Gorky in Chinese science was shaped, using one of its parts as critical literary and scientifi works on Gorky drama, starting from the moment the audience learned about the plays of the Soviet classic in the 30s of the 20th century. The most significant Chinese translation of Gorky's plays and their publications are considered. An important aspect of the reception of Gorky drama from the cultural Chinese audience is its performance on the stages of theaters in the People’s Republic of China, therefore the stage interpretation of Gorky’s texts is also in the field of attention of the research. In conclusion, today Gorky in China is experiencing a new upsurge and dramaturgy of the writer, as well as its tradition and bizarre reflection in the plays of modern authors are regularly becoming the subject of scientific interest of Chinese Russianists.